High-definition velocity-space tomography of fast-ion dynamics. (19th August 2016) - Salewski, M.; Geiger, B.; Jacobsen, A.S.; Hansen, P.C.; Heidbrink, W.W.; Korsholm, S.B.; Leipold, F.; Madsen, J.; Moseev, D.; Nielsen, S.K.; Nocente, M.; Odstrčil, T.; et al.
Abstract: Velocity-space tomography of the fast-ion distribution function in a fusion plasma is usually a photon-starved tomography method due to limited optical access and signal-to-noise ratio of fast-ion D α (FIDA) spectroscopy as well as the strive for high-resolution images. In high-definition tomography, prior information makes up for this lack of data. We restrict the target velocity space through the measured absence of FIDA light, impose phase-space densities to be non-negative, and encode the known geometry of neutral beam injection (NBI) sources. We further use a numerical simulation as prior information to reconstruct where in velocity space the measurements and the simulation disagree. This alternative approach is demonstrated for four-view as well as for two-view FIDA measurements. The high-definition tomography tools allow us to study fast ions in sawtoothing plasmas and the formation of NBI peaks at full, half and one-third energy by time-resolved tomographic movies.